Applicability of Small-Molecule Inhibitors in the Study of Peptidyl Arginine Deiminase 2 (PAD2) and PAD4 - Martín Monreal, María Teresa; Rebak, Alexandra Stripp; Massarenti, Laura; Mondal, Santanu; Šenolt, Ladislav; Ødum, Niels; Nielsen, Michael L.; Thompson, Paul R.; Nielsen, Claus H.; Damgaard, Dres (Frontiers in Immunology, 2021)
Citrullination, the conversion of peptidyl-arginine into peptidyl-citrulline, is involved in the breakage of self-tolerance in anti-CCP-positive rheumatoid arthritis. This reaction is catalysed by peptidyl arginine deiminases (PADs), of which PAD2 and PAD4 are thought to play key pathogenic roles. Small-molecule PAD inhibitors such as the pan-PAD inhibitor BB-Cl-amidine, the PAD2-specific inhibitor AFM-30a, and the PAD4-specific inhibitor GSK199 hold therapeutic potential and are useful tools in studies of citrullination. Using an ELISA based on the citrullination of fibrinogen, we found that AFM-30a inhibited the catalytic activity of PADs derived from live PMNs or lysed PBMCs and PMNs, and of PADs in cell-free synovial fluid samples from RA patients, while GSK199 had minor effects. In combination, AFM-30a and GSK199 inhibited total intracellular citrullination and citrullination of histone H3 in PBMCs, as determined by Western blotting. They were essentially non-toxic to CD4+ T cells, CD8+ T cells, B cells, NK cells and monocytes at concentrations ranging from 1M to 20 M, while BB-Cl-amidine was cytotoxic at concentrations above 1 M, as assessed by flow cytometric viability staining and by measurement of lactate dehydrogenase released from dying cells. In conclusion, AFM-30a is an efficient inhibitor of PAD2 derived from PBMCs, PMNs or synovial fluid. AFM-30a and GSK199 can be used in combination for inhibition of PAD activity associated with PBMCs, but without the cytotoxic effect of BB-Cl-amidine. This suggests that AFM-30a and GSK199 may have fewer off-target effects than BB-Cl-amidine and therefore hold greater therapeutic potential.